Gingival Margin Damage During Supragingival Dental Polishing by Inexperienced Operator—Pilot Study - Blagovesta Yaneva; Petar Shentov; Dimitar Bogoev; Maria Mutafchieva; Stela Atanasova-Vladimirova; Kiril Dimitrov; Diyana Vladova (Journal of Functional Biomaterials)
Background: Supragingival polishing is a crucial part of nonsurgical periodontal therapy. In recent years, air polishing has been used for this purpose, introducing different polishing powders. The purpose of the following study was to investigate the damage to the gingival margin during air polishing by an inexperienced operator. Methods: Five porcine models were polished by means of three different polishing powders: calcium carbonate, sodium bicarbonate, and erythritol. Their impact on the gingival margin was examined by means of histological and scanning electron microscopical observations and compared to healthy samples and samples polished with a polishing brush and paste. Results: The histological observations revealed superficial to minor lesions limited in the epithelium by all the groups tested. Both examination protocols demonstrated less invasiveness of the erythritol-based polishing powder. Conclusions: Within the limitations of the present study, it could be concluded that air polishing is a safe instrumentation method for periodontal therapy even in inexperienced hands when the exact protocol is followed. The erythritol-based polishing powder seems to provide less of an impact on the gingival margin.